Investigation of impedance-based fault location techniques in power system network / Tan Feng Jie - Tan, Feng Jie (2019)
Power transmission network delivers the electrical power from one substation to another over long distance lines often passing through remote areas with limited accessibility. Identify the fault location accurately helps to restore the power supply in short period and reduce the economic loss due to prolonged rectification works and power outage. A number of one-ended impedance-based fault location methods have been developed to estimate the fault distance in transmission network. However it is widely reported that the accuracy of impedance-based fault location methods is influenced by a number of system parameters. As such, it is essential to understand the effect of system parameters on the accuracy of fault location methods when selecting the fault location method for transmission system. This research project presents the investigation on the effect of the 5 systems parameters on the accuracy of the 4 one-ended impedance-based fault location methods. 5 case studies represent the effect of 5 system parameters are simulated using the transmission network model developed in MATLAB SIMULINK. The simulated voltage and current waveforms are applied to the algorithms of 4 fault locations methods to compute the estimated fault distance. The estimated fault distances are evaluated using relative error based on total line length to determine the accuracy. The accuracy and performance of one-ended impedance-based fault location methods in the 5 case studies are discussed and compared in this report. The summary of results and the recommendations for one-ended impedance-based fault location methods are also provided in this report as reference for readers.